Changes in intraocular pressure in study and fellow eyes in the IVAN trial. Issue 12 (12th April 2016) - Foss, Alexander J E; Scott, Lauren J; Rogers, Chris A; Reeves, Barney C; Ghanchi, Faruque; Gibson, Jonathan; Chakravarthy, Usha
Abstract : Purpose: To describe changes in intraocular pressure (IOP) in the 'alternative treatments to I nhibit V EGF in A ge-related choroidal N eovascularisation (IVAN)' trial (registered as ISRCTN92166560 ). Design: Randomised controlled clinical trial with factorial design. Participants: Patients (n=610) with treatment naïve neovascular age-related macular degeneration were enrolled and randomly assigned to receive either ranibizumab or bevacizumab and to two regimens, namely monthly (continuous) or as needed (discontinuous) treatment. Methods: At monthly visits, IOP was measured preinjection in both eyes, and postinjection in the study eye. Outcome measures: The effects of 10 prespecified covariates on preinjection IOP, change in IOP (postinjection minus preinjection) and the difference in preinjection IOP between the two eyes were examined. Results: For every month in trial, there was a statistically significant rise in both the preinjection IOP and the change in IOP postinjection during the time in the trial (estimate 0.02 mm Hg, 95% CI 0.01 to 0.03, p<0.001 and 0.03 mm Hg, 95% CI 0.01 to 0.04, p=0.002, respectively). There was also a small but significant increase during the time in trial in the difference in IOP between the two eyes (estimate 0.01 mm Hg, 95% CI 0.005 to 0.02, p<0.001). There were no differences between bevacizumab and ranibizumab for any of the three outcomes (p=0.93, p=0.22 and p=0.87, respectively). Conclusions: Anti-vascular endothelial growth factor agents induce increases in IOP of small and uncertain clinical significance. Trial registration number: ISRCTN92166560.